DIPLOMASI PERUBAHAN IKLIM INDONESIA PADA MASA PANDEMI COVID-19 - Seftina Kuswardini; Sannya Pestari Dewi; Frindhy Wara Limaran (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2022)
The existence of the COVID-19 pandemic that has hit all regions of the world, including Indonesia, has had a significant impact on people's mobility. The economic impact is the most felt during this pandemic, especially the reduction in industrial and manufacturing activities, but the reduction in industrial activity is considered to have a good impact on environmental security because it can reduce the amount of gas emissions. This situation should be a good opportunity for Indonesia in its efforts to tackle climate change. However, during the implementation of COP-25, it failed to reach an agreement in article 6 of the Paris Agreement and could not describe concrete actions from climate action and Indonesia only managed to take points on the oceanic issue at the meeting, while Indonesia is a pioneer country for climate change action in the G countries. -20. This raises the question of the extent of Indonesia's diplomatic efforts and commitment to climate change. This study aims to see and analyse the direction of Indonesia's climate diplomacy during the COVID-19 pandemic. The Indonesian Pavilion was a form of Indonesian diplomacy during COP-26 in the midst of the Covid-19 pandemic.